2011
DOI: 10.1590/s0124-00642011000500014
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome da fragilidade biológica em idosos: revisão sistemática

Abstract: RESUMOObjetivo O objetivo desse estudo foi identificar a prevalência e as estratégias de avaliação da Síndrome da Fragilidade Biológica em Idosos. Metodologia Para o desenvolvimento deste estudo foi realizada uma busca em base de dados eletrônica (Medline/Pubmed) e lista de referências dos artigos identificados, utilizando os seguintes descritores, na língua inglesa: "frailty e "frail" conjugados com os termos "elderly", "aging" e "prevalence". Estes termos/descritores foram combinados usando os operadores lóg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
11
2
3
Order By: Relevance
“…There is a correlation between frailty and sex, with the prevalence higher in women than in men (6,12,15) , in contrast to the data in this study, no statistically significant association was found between the sex and the prevalence of frailty. Possibly this is related to the reason for hospitalization, with the men having more severe and disabling conditions.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…There is a correlation between frailty and sex, with the prevalence higher in women than in men (6,12,15) , in contrast to the data in this study, no statistically significant association was found between the sex and the prevalence of frailty. Possibly this is related to the reason for hospitalization, with the men having more severe and disabling conditions.…”
Section: Discussioncontrasting
confidence: 92%
“…(6) have been validated for elderly people from this age group. In a review study (12) , all publications had a population range age of equal to or older than 65. HSVP hospital is a tertiary teaching hospital, with macro-regional scope com, integrated into the SUS public health system and has 617 inpatient beds.…”
Section: There Is Still Not Yet a Scientific Consensus Regarding The mentioning
confidence: 99%
“…These data corroborate the results of other studies found in the literature. The prevalence of frailty syndrome in research around the world with the use of this phenotype, were found in percentages ranging from 5 to 20% (26)(27) . The increasing number of publications concerning the frailty syndrome in recent years refers to the growing interest in the matter, since frailty can be considered a public health problem, although it may be prevented or even reversed when treated early (27).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty, according to the phenotype (7) , is from 6.9% to 21%. Research showed that, for females, this state was higher, from 6.8% to 22%, and for males, from 4% to 19.2% (12) . Measuring this syndrome, using different models used in Primary Health Care, a prevalence of 4% to 59.1% was found, with populations in Southeastern Europe, Hispanics and African-Americans being the most affected (13) .…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, it was observed that the prevalence of falls ranged from 8.2% (28) to 93.0% (32) . It should be noted that frailty was measured with different measurement instruments, since it is a great challenge for researchers to obtain an instrument that can be considered as a "gold standard" to accurately compare the results (12) . Frailty was evaluated with eight instruments: the CSBA Index (41) , with nine items; The SOF Index (37) with three; The CHS Index (7) , with five; The LASA Frailty Instrument (42) , with nine; The FRAIL Index (43) , with five; The Edmonton Frail Scale (11) with nine; The VES-13 (44) , with 13; and SNAC Instrument (45) , with three domains.…”
Section: Authorsmentioning
confidence: 99%